A specific profile of luteal phase progesterone is associated with the development of premenstrual symptoms. (January 2017) - Lovick, Thelma A.; Guapo, Vinicius G.; Anselmo-Franci, Janete A.; Loureiro, Camila M.; Faleiros, Maria Clara M.; Del Ben, Cristina M.; Brandão, Marcus L.
Highlights: Women with sharp decline in luteal phase progesterone developed premenstrual symptoms. Women with gradual decline in luteal phase progesterone had no premenstrual dysphoria. Rate of progesterone metabolism linked to development of premenstrual dysphorias. Abstract: There is a consensus that the development of premenstrual dysphoric states is related to cyclical change in gonadal hormone secretion during the menstrual cycle. However, results from studies seeking to link symptom severity to luteal phase progesterone concentration have been equivocal. In the present study we evaluated not only the absolute concentrations of progesterone but also the kinetics of the change in progesterone concentration in relation to development of premenstrual symptoms during the last 10 days of the luteal phase in a population of 46 healthy young adult Brazilian women aged 18–39 years, mean 26.5 ± 6.7 years. In participants who developed symptoms of premenstrual distress, daily saliva progesterone concentration remained stable during most of the mid-late luteal phase, before declining sharply during the last 3 days prior to onset of menstruation. In contrast, progesterone concentration in asymptomatic women underwent a gradual decline over the last 8 days prior to menstruation. Neither maximum nor minimum concentrations of progesterone in the two groups were related to the appearance or severity of premenstrual symptoms. We propose that individual differences in the kinetics of progesterone secretion and/or metabolism may confer differential susceptibility to the development of premenstrual syndrome.